Interview with Arnaldo Rodríguez Espinoza. Challenges of Civic Education in Costa Rica - Rodríguez Espinoza, Arnaldo (2018)
This is an interview that refers to some challenges of Civic Education in Costa Rica. For the specialist in Civic Education is a discipline that allows us to face the challenges of real society, the choice must have as objective the formation of thinking and acting subjects. Another challenge is to define a curriculum according to what is expected or intended to be developed from their specialty and not become a discipline that accommodates a number of topics, which are even repetitive with the Social Studies program. In addition, Civic Education must be promoted in relation to the context of the students and reinforce a more formative evaluation.